(untitled) (Global Scientific Review, 2025)
This article is devoted to the problem of monitoring the quality of education in the system of advanced training of teachers in the vocational education system. The article presents monitoring as one of the ways to study the quality of education in the advanced training system, and examines it from a methodological standpoint: the essence of monitoring and its factors is revealed, the relevance of its widespread implementation in the advanced training system is determined, and the principles, didactic features, and functions of monitoring are highlighted.